2021
DOI: 10.1007/s00345-020-03585-2
|View full text |Cite
|
Sign up to set email alerts
|

PHI density prospectively improves prostate cancer detection

Abstract: Purpose To evaluate the Prostate Health Index (PHI) density (PHID) in direct comparison with PHI in a prospective large cohort. Methods PHID values were calculated from prostate-specific antigen (PSA), free PSA and [− 2]proPSA and prostate volume. The 1057 patients included 552 men with prostate cancer (PCa) and 505 with no evidence of malignancy (NEM). In detail, 562 patients were biopsied at the Charité Hospital Berlin and 495 patients at the Sana Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…For the same PSA range used in our study, be- PSA prostate-specific antigen, PHI prostate health index, PSAD prostate-specific antigen density, PHID prostate health index density, CI confidence interval, PPV positive predictive value, NPV negative predictive value, PCa prostate cancer, csPCa clinically significant prostate cancer. and PHID (0.835) quite similar to those we have found in our study cohort (PSAD: 0.776; PHID: 0.823) [16].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For the same PSA range used in our study, be- PSA prostate-specific antigen, PHI prostate health index, PSAD prostate-specific antigen density, PHID prostate health index density, CI confidence interval, PPV positive predictive value, NPV negative predictive value, PCa prostate cancer, csPCa clinically significant prostate cancer. and PHID (0.835) quite similar to those we have found in our study cohort (PSAD: 0.776; PHID: 0.823) [16].…”
Section: Discussionsupporting
confidence: 90%
“…For the same diagnostic sensitivity of approximately 90%, PHID can provide only a small gain in specificity when compared to PHI alone (39.6% versus 35.8%). Stephan et al performed a similar study, however considering only the GS to define csPCa (GS ≥ 7), and concluded that PHI and PHID performed equally in detecting csPCa, based only on the values of the AUCs [16]. Our results also show almost the same performance between PHI and PHID for csPCa detection.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A large retrospective cohort study demonstrated that PHID had similar AUC as PHI and had a small advantage on decision curve analysis than PHI alone in predicting overall PCa (54). Stephan et al found PHID had significantly larger AUC than PHI in predicting overall PCa but no significant difference from PHI if aiming for csPCa (55). In our study, the AUC of PHID is significantly better than PHI in predicting csPCa (p=0.004, Figure 1B).…”
Section: Discussionsupporting
confidence: 37%
“…It is necessary to comprehensively consider the situation of the patient and then fit different image parameters to optimize the predicting model. Currently, though PHID has been proven to better identify PCa within the PSA gray zone ( 23 ), the modality still possesses limitations. Above all, bias in results will come upon when using the tPV as a normalized control for PHID or PSAD.…”
Section: Introductionmentioning
confidence: 99%